2015
DOI: 10.1016/j.earlhumdev.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

The second to fourth digit ratio (2D:4D) in Saudi boys with autism: A potential screening tool

Abstract: This study demonstrates a significantly lower 2D:4D ratio in Saudi boys with autism, which indirectly suggests that these boys were exposed to high levels of prenatal FT. Accordingly, prenatal exposure to high levels of FT is a risk factor for the development of autism, and the postnatal measurement of the 2D:4D ratio could be a potential screening tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 18 publications
2
22
0
1
Order By: Relevance
“…Evidence for the effects of fT also come from studies of girls with congenital adrenal hyperplasia (CAH), children of women with polycystic ovarian syndrome (PCOS), and females with male co-twins, all of whom are exposed to higher than normal levels of fT. Correlation of increased fT in these populations with autistic trait scores and ASD diagnosis was demonstrated in many studies but not all [41,53,58,6674]. A recent study found that at 12 and 36 months, there was no relationship between levels of fT or other androgens in umbilical cord blood of children with older siblings diagnosed with ASD, and autistic traits, except in a small subset of children whose older sibling was a female with ASD [75].…”
Section: Sex Hormone Theory: Are Fetal Testosterone Levels Linked To mentioning
confidence: 99%
“…Evidence for the effects of fT also come from studies of girls with congenital adrenal hyperplasia (CAH), children of women with polycystic ovarian syndrome (PCOS), and females with male co-twins, all of whom are exposed to higher than normal levels of fT. Correlation of increased fT in these populations with autistic trait scores and ASD diagnosis was demonstrated in many studies but not all [41,53,58,6674]. A recent study found that at 12 and 36 months, there was no relationship between levels of fT or other androgens in umbilical cord blood of children with older siblings diagnosed with ASD, and autistic traits, except in a small subset of children whose older sibling was a female with ASD [75].…”
Section: Sex Hormone Theory: Are Fetal Testosterone Levels Linked To mentioning
confidence: 99%
“…This ratio is stable throughout life from at least the age of two years [4] The prenatal period is known to be critical for development and determination of future health. Digit ratio has been suggested as a marker of in-utero hormonal environment, and human and animal studies have found an association between the digit ratio and adverse health outcomes, including Autism [5], coronary heart disease [6] and breast cancer [7]. Synthetic environmental contaminants known as endocrine disrupting agents have been shown to interact with or mimic endogenous endocrine hormones, possibly affecting the digit ratio [8].…”
Section: Introductionmentioning
confidence: 99%
“…In children with autism spectrum disorder, which is associated with a prenatal exposure to high concentrations of testosterone, a lower 2D:4D has been observed (10). An association between 2D:4D and gastric cancer (11), knee and hip osteoarthritis (12), and prostate cancer (13) has also been reported.…”
Section: Introductionmentioning
confidence: 99%